Electronic properties of orthorhombic LiGaS2 and LiGaSe 2 - Reshak, Ali H.; Auluck, S.; Kityk, I. V.; Yarub K.A, Al-Douri; Khenata, R.; Bouhemadou, A. (Springer Berlin/Heidelberg, 2009)
Link to publisher's homepage at http://www.springerlink.com/content/mqq44r6183562kn2/